Chemical Composition, Antibacterial, Antioxidant, and Cytotoxicity Activities of Essential Oil of Leaf of Ageratina adenophora (Spreng.) R.M. King and H. Rob. - Thapa, Arjun; Maharjan, Binita; Bharati, Samjhana; Shrestha, Timila; Homagai, Puspa Lal; Bhattarai, Deval Prasad; Shrestha, Ram Lal Swagat (Journal of Nepal Chemical Society, 2024)
Modern medicine recognizes the therapeutic applications of medicinal plants, which are utilized in indigenous therapies. Ageratina adenophora (Banmara) is an invasive plant growing in tropical and subtropical regions, traditionally used for treating wounds, sleeping disorders, jaundice, ulcers, etc. Using Clevenger apparatus for hydro-distillation, the essential oil was extracted, and gas chromatography-mass spectrometry (GC-MS) was used to determine its chemical constituents. GC-MS analysis of essential oil showed 14 possible compounds in which α-Muurolol (24.56%) was found to be most abundant. The essential oil exhibited a total phenolic content of 53.42 mg of gallic acid equivalent per gram of dry extract, while the total flavonoid content was determined to be 3.37 mg of quercetin equivalent per gram of dry extract. Essential oil of A. adhenophora showed a high antibacterial action against Staphylococcus aureus of ZOI of 12 mm. The antioxidant assay revealed weak activity of essential oil of IC50 17.21 mg/mL, while the brine shrimp lethality assay revealed its LC50 value to be 64.56 μg/mL.